동시대 공예이론의 전개에 관한 연구 -하워드 리사티와 래리 샤이너의 이론을 중심으로 - 김지은; Ji Eun Kim; 박일호; 교신저자; Il Ho Park (기초조형학연구, 2016)
본 논문은 동시대 공예이론에 대한 것이다. 전통적인 공예의 정의는``실용적인 물건에 장식적인 가치를 부여한 것``이었다. 그러나 1960년대 초부터 시작된 모더니즘 미술의 영향으로 공예는 새로운 실험을 통해 다양한 조형성을 보여주면서 독자적인 예술의 영역이 되었다. 하지만 광범위한 공예활동을 설명할 수 있는 비평담론의 기반은 여전히 취약하다. 이러한 점에서 본 논문의 목적은 동시대 공예이론의 연구를 통해 공예를 분석할 수 있는 기반을 마련하는 것이다. 이를 위해 우선 1960년대 이후 미술에서의 변화가 공예에 미친 영향을 알아보고, 동시대 공예의 전개 양상을 살펴보았다. 다음으로 하워드 리사티와 래리 샤이너의 이론을 통해 동시대 공예현상을 설명하였다. 리사티는 공예와 예술의 분리를 비판하면서 공예와 순수예술의 논쟁이 갖고 있는 미학적 문제에 접근한다. 그리고 기능 없이 오브제화된 공예작품을 ``비평적 공예 오브제``라 칭하고 예술로 정당화 시킨다. 이에 반해 샤이너는 순수예술을 18세기에 서구가 창안해낸 역사적 구성물로 보고 문화사적 관점에서 공예를 설명한다. 그리고 순수예술 체계를 넘어서 모든 것이 하나로 통합된``포스트 예술체계``를 제안 하는데, 그 체계 안에서 공예는 다양한 문화적 실천의 상위개념이 된다. 리사티의 관점은 예술로서 공예를 설명하고 있지만 공예를 다시 이분화 시키는 한계를 갖고 있다. 반면, 샤이너의 관점은 전통공예품에서부터 비평적 예술작품에 이르기까지 광범위한 공예활동을 설명하는데 적절하다. 이런 맥락에서 필자는 다양한 동 시대 공예현상을 분석하고, 이론의 부재로 저평가 받아온 공예에 대한 인식을 개선하여 공예의 지평을 넓혀주는데 샤이너의 관점이 더 큰 의의가 있다고 생각 한다. This essay shows ``the theory of contemporary craft``. The definition of traditional craft provides ``things for practical use with decorative value``. The craft influenced by modernism art since the early 1960`s has been an individual artistic field showing a variety of molding by a new experimentation. However, the base of critical discourse which can explain a wide range of craft activity is very poor. From this point of view, the main purpose of this essay is to prepare the base on which we can analyze craft by studying the contemporary craft theory. To do this, first, I researched how the change of fine art had an effect on craft and studied how the contemporary craft begun. Next, I tried to explain contemporary craft activity based on the theory of Howard Risatti and Larry Shiner. Risatti criticizes the separation of craft and art and approaches the artistic issue in the dispute between craft and fine art. He also calls craft work as an object without function ``critical object of craft`` and justifies it as art. On the contrary, Shiner considers fine art as historical structure that the West created in the 18th century and explains craft with a view of cultural history. He also suggests craft should be the ``post art system`` unified as a whole one beyond the system of fine art. He argues that as a result, craft becomes a higher concept of different cultural practice in the system. Even though Risatti`s viewpoint is that he explains craft as art, there is a limitation that he simply bisected craft. On the other hand, Shiner`s is appropriate for explaining a variety of craft activity including critical art work as well as traditional craft work. In this respect, I think Shiner`s viewpoint has more significant meaning setting up a theoretical frame to analyze diverse contemporary phenomenon of craft and improving the concept of craft devaluated because of the poor theoretical background.